PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN LARUTAN PENYANGGA DI KELAS XI MIPA SMA NEGERI 7 PEKANBARU - Nabila, Rosena Putri; Amran, Elva Yasmi; Susilawati, Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims to improve student learning achievement on the subject of buffer solution in class XI MIPA SMAN 7 Pekanbaru. This type of research is an experimental study with a pretest-posttest design. The research was conducted at SMAN 7 Pekanbaru. The sample from the study was students of class XI MIPA 1 as an experimental class and students in class XI MIPA 2 as a control class. The experimental class is the class applied to the TTW Type Cooperative Learnings while the control class is not treated. The data analysis technique used is the t-test. Based on the results of the data analysis test, tcount> ttable is 2,19> 1,67, meaning that the application of TTW Type Cooperative learning model can improve student learning achievement on the subject of buffer solution in class XI MIPA 1 of SMA Negeri 7 with categories of achievement improvement learning in the experimental class based on Score (N-Gain) is high, which is 0,73.Key Words: Think Talk Write (TTW) Type Cooperative Learning Model, Learning Achievement, Buffer Solution.